2020
DOI: 10.1590/0034-7167-2018-0918
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors: differences between ethnic groups

Abstract: ABSTRACT Objectives: to compare the metabolic, anthropometric, tobacco and alcohol consumption indicators considered as risk factors for cardiovascular diseases, as well as the demographic and socioeconomic characteristics between indigenous from Rio Negro, Sateré-Mawé, mixed-race/black and white people living in the city of Manaus. Methods: a cross-sectional observational study guided by the STROBE tool. There was a sample of 191 adults of both sexes. Anthropometric measurements, blood pressure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
1
3
0
2
Order By: Relevance
“…The social vulnerability and low schooling found among the Munduruku under study were similar to those of other ethnic groups, which also showed the direct impact of the social and economic determinants on the mechanisms and distribution of diseases, including cardiovascular ones ( 5 , 29 ) .…”
Section: Discussionsupporting
confidence: 66%
“…The social vulnerability and low schooling found among the Munduruku under study were similar to those of other ethnic groups, which also showed the direct impact of the social and economic determinants on the mechanisms and distribution of diseases, including cardiovascular ones ( 5 , 29 ) .…”
Section: Discussionsupporting
confidence: 66%
“…[100][101][102][103] Most studies in the United Kingdom also report a higher prevalence in Black and South Asian adults than White adults. [106][107][108] Studies from other countries, including both developed [109][110][111] and developing countries, [112][113][114][115][116] have generally found that ethnic/racial minorities have higher levels of prevalent hypertension than the majority population.…”
Section: Ethnic/racial Differences Hypertension Prevalence By Ethnici...mentioning
confidence: 99%
“…A study that investigated cardiovascular risk factors among different ethnic groups, living in the same urban area of Manaus (Amazonas), identified that, although the prevalence of SAH among the indigenous people was lower than in white-skinned (62.5%) and brown-/ black-skinned (60.7%) individuals, that for pre-hypertension and hypertension was 28.6% among the Sateré-Mawé and 46.5% among ethnic groups from the upper Rio Negro [39].…”
Section: Plos Onementioning
confidence: 99%